Sistem Informasi Pencatatan dan Pelaporan Pelayanan Kesehatan Berbasis Android di Kawasan Terpencil dan Sangat Terpencil - Syefira Salsabila (Jurnal Rekam Medis dan Informasi Kesehatan, 2019)
Health care is the right of every community to get service without exception, even though it is in an area that is difficult to reach due to geographical access. Mobile Health Services (PKB) is one of the innovations in equitable health services in remote and very remote areas. The process of recording and processing data is generally held also on PKB is still done manually. Recording that is still running in handwriting causes many obstacles in the process of processing, searching, and making reports on health service activities. The purpose of this study is to identify and develop information systems for recording and reporting on maternal and child health service activities at PKB. This research method uses Action Research. This design was chosen because it would delve deeply into the process and management of the development of Android-based applications for PKB. The results of this study present that the use of android-based mobile phones as a tool in data collection for the implementation of recording and reporting of mother and child activities can be carried out offline. This prototype information system made the process more efficient in term of time, especially when the data is uploaded to a properly administered server, makes the data much more secure, more effective to use for mobile health clinic team or health provider for data reporting.